Revisiting behaviour of monometallic catalysts in chemical vapour deposition synthesis of single-walled carbon nanotubes - Rong Xiang; Shigeo Maruyama (Royal Society Open Science, 2018)
A catalyst is essential for the controlled synthesis of single-walled carbon nanotubes (SWNTs) by chemical vapour deposition (CVD). However, it is difficult to observe these nanosized particles in their original forms and in a statistical manner, which has resulted in a vague understanding of the behaviours of these particles. We present a technique to solve this long-standing issue. The key is to have an MEMS fabricated suspended SiO2 layer, which is thick enough to support catalyst deposition and nanotube growth but thin enough to allow electron beams to transit. On a 20 nm SiO2 film, we confirm that catalyst can be observed at an atomic resolution, and the catalyst–SWNT junctions can also be routinely observed. As a demonstration of this technique, we revisited the behaviour of monometallic catalysts through a systematic investigation of the size, chemical state and crystal structure of particles before and after high-temperature CVD. The active catalyst is found to follow a tangential growth mode, while the inactive catalyst is divided into three mechanisms: size growth, metal loss and inappropriate precipitation. The latter two mechanisms were not possible to observe by previous techniques.